Klebelsberg Kunó és a sárospataki Angol Internátus - Barta, Róbert (Gerundium, 2019)
Kuno Klebelsberg and the English College of Sárospatak. The study analyses historical aspects and relationships between the English College of Sárospatak (1931–1947), as one of the practical outcome of Kuno Klebelsberg’s education policy and the general features of the cultural and education policy of the time. The making of the College served threefold aims: strenghten the revisionist policy of the regime, emphasize new features of cultural and education policy (cultural superiority, new nationalism) and enforce vivid British–Hungarian relationships. The existence of the College also helped to represent the local and religious interests in the nationwide political theatre of balancing Hungarian Churches. The author reviews the acticity of Kuno Klebelsberg in this project-eg. his speeches, articles, visits to Sárospatak- and also the foundation and educational work of the College. The study emphasizes that tanks to the two decades existence of the College, new Hungarian elite generations were grown up with a deep belief that the only future of Hungary is in the family of nations of western civilization.